Cranio-facial sutures of the black-capped squirrel monkey Saimiri boliviensis (Primates: Cebidae): Gross morphology and postnatal ontogeny - Flores, David Alfredo (2012)
Cranial suture closures in the black-capped squirrel monkey Saimiri boliviensis were examined. Sequences in closure and morphological changes during ontogeny were interpreted as indicators of skeletal strains and age. Some sutures seem to be more reliable determinants of skeletal age than others. As found in other species of Saimiri , the palatal and rostral portion of the maxillo-premaxillaris suture show regular fusion associated with earlier age. The predictable sequence was: (1) maxillo-premaxillary and zygomatico frontal (orbital part), (2) transverse maxillo-premaxillary, (3) spheno-occipital, (4) internasalis, (5) palatal portion of interpremaxillar, denoting a relatively conservative pattern in the genus. However, most sutures were patent still in older specimens. The ontogenetic variation in the suture morphology was pointed to the acquisition of complex interdigitation and overlapping. The general trend detected indicates that the ectocranial sutures of S. boliviensis acquire progressively more capacity for strength support because the crescent interdigitation of sutures functionally committed with mastication and growth, as those of vault, rostrum and palate.